Digital Marketing Innovation and Marketing Performance: The Mediating Role of Business Process Agility - Avianita Rachmawati; Luisa De Marilak Manggo (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze the mediating role of business process agility in the effect of digital marketing innovation on marketing performance. This study employs a quantitative method with a descriptive research design, involving a sample of 141 respondents selected through purposive sampling. Data collection was conducted via a Google Forms questionnaire, and the data were analyzed using Partial Least Squares (PLS-SEM). The results indicate that Digital Marketing Innovation has a significant positive effect on marketing performance (β = 0.363; p = 0.004), Business Process Agility has a significant positive effect on marketing performance (β = 0.442; p = 0.001), and partially mediates the relationship between Digital Marketing Innovation and marketing performance (β = 0.340; p = 0.001). Digital innovation is proven to be more effective when supported by business process agility, enabling culinary SMEs to enhance their competitiveness in the digital era. This study adds an empirical foundation regarding the importance of digital marketing innovation and business process agility in driving marketing performance. In practice, this enables SMEs to be more responsive to customer needs while generating increased revenue and expanding market reach.